Baby dumping scenario in Malaysia: an analysis on its similarity to infanticide or murder under the law of Malaysia - Mohd, Azizah; Mohd Noor, Fauziah (Serials Publications (P) Ltd., 2016)
The scenario of dumping of babies in Malaysia is alarming and increasing day by day. The babies were dumped everywhere, in the dustbin, on the street, in the toilet, in the bushes etc. In many occasion they were found dead and restless even though in several cases they are found alive. This research examines baby dumping scenario in Malaysia and its position under Islamic and civil law. Examination includes analysis on whether baby dumping constitutes infanticide or murder under both laws. The practice of killing babies during the period before Islam (jahiliyyah period) especially in Arabian Peninsular will also be highlighted in particular to provide an overview and comparison as to the classical practice of abandoning children and infanticide with the modern practice. Finally, analysis will also be done on adequacy of the law in providing for punishment of abandoning babies in both cases where the babies were found dead and alive.